2017
DOI: 10.1007/s10802-017-0276-7
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and Children’s ADHD in a Family System

Abstract: ADHD symptoms "run in families". However, relatively little is known about the ways in which parents' symptoms might additively and interactively work with the parenting environment, to influence (and be influenced by) the developmental trajectory of symptoms in children and adolescents. In this commentary on the special section addressing this gap in knowledge, emphasis is placed on the importance of replicating and extending family-wide studies of ADHD symptoms and etiology. The current papers exemplify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…This mediating role suggests that parents who have a better perception of their own parenting skills feel more confident about their ability to cope with any possible adversities in the family system, including parental stress. The results of our study could be interpreted in terms of bidirectional systemic regulations, as indeed suggested by authors such as Breaux and Harvey (2018) and Deater-Deckard (2017). Supporting this systemic view, Ben-Naim et al (2019) reported a mediating role of parental stress and self-efficacy between children's ADHD and marital satisfaction.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This mediating role suggests that parents who have a better perception of their own parenting skills feel more confident about their ability to cope with any possible adversities in the family system, including parental stress. The results of our study could be interpreted in terms of bidirectional systemic regulations, as indeed suggested by authors such as Breaux and Harvey (2018) and Deater-Deckard (2017). Supporting this systemic view, Ben-Naim et al (2019) reported a mediating role of parental stress and self-efficacy between children's ADHD and marital satisfaction.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, parental stress has been associated with attention deficits, poor self-regulation and behaviour problems among children (Barroso et al 2018). In this sense, Deater-Deckard (2004) highlights that parenting stress could arise from trying to adapt to the demands of parenthood and that it could also be influenced by parental and child adjustment.…”
mentioning
confidence: 99%
“…However, the rate of the included mothers was higher than that of the fathers, which was consistent with a study in Mexico [ 24 , 41 ] and meant that mothers are always the primary caregivers of the children. The caregivers of children with ADHD experience great pressure [ 42 ]. From this point of view, the mental health status of those mothers who have children with ADHD should receive more attention and acquire more support.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse birth outcomes are associated with ADHD in offspring [ 58 , 59 ]. Thirdly, young parents tend to have a history of hyperactivity problems, and the genetic susceptibility to ADHD in young parents may be transmitted to their offspring [ 60 , 61 ]. Moreover, the impulsivity associated with ADHD might lead to an increased rate of unplanned pregnancy, making young people become parents at an earlier age [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%